Increasing postpartum family planning uptake through group antenatal care: a longitudinal prospective cohort design - Jody R. Lori; Meagan Chuey; Michelle L. Munro-Kramer; Henrietta Ofosu-Darkwah; Richard M. K. Adanu (BMC, 2018)
Abstract Background Despite significant improvements, postpartum family planning uptake remains low for women in sub-Saharan Africa. Transmitting family planning education in a comprehensible way during antenatal care (ANC) has the potential for long-term positive impact on contraceptive use. We followed women for one-year postpartum to examine the uptake and continuation of family planning following enrollment in group versus individual ANC. Methods A longitudinal, prospective cohort design was used. Two hundred forty women were assigned to group ANC (n = 120) or standard, individual care (n = 120) at their first ANC visit. Principal outcome measures included intent to use family planning immediately postpartum and use of a modern family planning method at one-year postpartum. Additionally, data were collected on intended and actual length of exclusive breastfeeding at one-year postpartum. Pearson chi-square tests were used to test for statistically significant differences between group and individual ANC groups. Odds ratios and adjusted odds ratios were calculated using logistic regression. Results Women who participated in group ANC were more likely to use modern and non-modern contraception than those in individual care (59.1% vs. 19%, p < .001). This relationship improved when controlled for intention, age, religion, gravida, and education (AOR = 6.690, 95% CI: 2.724, 16,420). Women who participated in group ANC had higher odds of using a modern family planning method than those in individual care (AOR = 8.063, p < .001). Those who participated in group ANC were more likely to exclusively breastfeed for more than 6 months than those in individual care (75.5% vs. 50%, p < .001). This relationship remained statistically significant when adjusted for age, religion, gravida, and education (AOR = 3.796, 95% CI: 1.558, 9.247). Conclusions Group ANC has the potential to be an effective model for improving the uptake and continuation of post-partum family planning up to one-year. Antenatal care presents a unique opportunity to influence the adoption of postpartum family planning. This is the first study to examine the impact of group ANC on family planning intent and use in a low-resource setting. Group ANC holds the potential to increase postpartum family planning uptake and long-term continuation. Trial registration Not applicable. No health related outcomes reported.